EARLY OUTCOMES AFTER SUTURE TAPE REINFORCEMENT OF QUADRICEPS TENDON AUTOGRAFT ACL RECONSTRUCTION IN ADOLESCENT ATHLETES. Issue 7 (30th July 2021) - Saper, Michael
Background: Recently, anterior cruciate ligament reconstruction (ACLR) with suture-tape reinforcement has been popularized for protection of the graft during the revascularization and remodeling phase of incorporation. To date, there are limited short-term data regarding the outcomes of suture tape reinforcement to ACLR. Furthermore, its use with quadriceps tendon autograft (QT) ACLR is limited. Purpose: The purpose of this study was to review the early, preliminary results of ACLR in adolescent patients using QT autograft with suture tape reinforcement (QT-SR). Methods: A retrospective review was performed of skeletally mature adolescent patients who underwent primary ACLR with all-soft tissue QT-SR since 2018. Surgeries were performed by a single surgeon using an all-inside technique. All patients followed the same standardized rehabilitation protocol. Twelve-month patient-reported outcome measures (PROMs) and complications were analyzed. PROMs included the Pediatric International knee Documentation Committee (Pedi-IKDC) Subjective Knee Evaluation Form, Lysholm knee scoring scale, and the Tegner activity level scale. Psychological readiness was assessed with the ACL-Return to Sport after Injury (ACL-RSI) scale. Results: 39 patients (24 girls, 15 boys) were identified. The mean age at the time of surgery was 15.7 ± 1.3 years (range, 13-18 years). 82% of patients were high school athletes. Soccer was the primary sport for 48.7% of patients. The mean graft diameter was 9.5 ± 0.4 mm. 51.3% of patients had concomitant meniscus repairs. The mean time to return-to-sport clearance was 10.1 ± 1.4 months. At 12 months, the mean postoperative Pedi-IKDC was 95.6 ± 4.0, the mean Lysholm score was 97.6 ± 3.9, and the mean Tegner score was 8.8 ± 0.9. All PROMs improved significantly compared to the preoperative scores (Pedi-IKDC: p = 0.003, Lysholm: p = 0.006, Tegner: p = 0.003). The mean ACL-RSI was 93.4 ± 4.7. Complications included return to surgery due to postoperative stiffness in two patients. There were no cases of postoperative instability, graft rupture, or contralateral ACL injury. Conclusion: QT-SR ACLR results in excellent clinical and patient-reported outcomes in adolescent athletes at 12 months follow-up. The long-term effect of QT-SR remains to be investigated.